Vection is Modulated by the Semantic Meaning of Stimuli and Experimental Instructions. (July 2014) - Ogawa, Masaki; Seno, Takeharu
Vection strength is modulated by the semantic meanings of stimuli. In experiment 1—even though vection stimuli were of uniform size, color, and luminance—when they also had semantic meaning as falling objects, vection was inhibited. Specifically, stimuli perceived as feathers, petals, and leaves did not effectively induce vection. In experiment 2 we used the downward motion of identical dots to induce vection. Participants observed stimuli while holding either an umbrella or a wooden sword. Results showed that vection was inhibited when participants held the umbrella and the stimuli was perceived as rain or snow falling. The two experiments suggest that vection is modulated by the semantic meaning of stimuli.